2007
DOI: 10.2109/jcersj.115.131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phenyltriethoxysilane Concentration in Starting Solutions on Thermal Properties of Polyphenylsilsesquioxane Particles Prepared by a Two-Step Acid-Base Catalyzed Sol-Gel Process

Abstract: Spherical polyphenylsilsesquioxane particles were prepared by a two-step acid-base catalyzed sol-gel process, in which various amounts of ethanol were used as a solvent to vary the concentration of phenyltriethoxysilane PhSi OEt 3 used as a starting alkoxide. The decrease in the PhSi OEt 3 concentration led to the decrease in the average molecular weight and glass transition temperature of the polyphenylsilsesquioxanes. Thus, the change of the PhSi OEt 3 concentration in the preparation of polyphenylsilsesquio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…However, less branched oligomers of low molecular mass (M w < 3000) exhibit a glass transition at 360 K (Figure 8). An endothermic change in a similar temperature range was observed for cross-linked poly(phenysilsesquioxane) particles obtained by a two-step acidbase catalysed sol-gel process [21,22,54]. T g transition was not sensitive to the thermal treatment during DSC analysis.…”
Section: Preparation Of Ph-lpsq-sio 2 Compositessupporting
confidence: 61%
“…However, less branched oligomers of low molecular mass (M w < 3000) exhibit a glass transition at 360 K (Figure 8). An endothermic change in a similar temperature range was observed for cross-linked poly(phenysilsesquioxane) particles obtained by a two-step acidbase catalysed sol-gel process [21,22,54]. T g transition was not sensitive to the thermal treatment during DSC analysis.…”
Section: Preparation Of Ph-lpsq-sio 2 Compositessupporting
confidence: 61%
“…On the other hand, we had regarded the PhSiO 3/2 particles as a homogeneous substance and reported that T g increased with the increased average molecular weight of the particles [16]. However, the relationship described above only represented the results for PhSiO 3/2 species with low molecular weight, which were soluble in EtOH.…”
Section: Introductionmentioning
confidence: 97%
“…As described above, a similar tendency was observed in the formation of solid particles. Our previous work 23) showed that T g of the PhSiO 3/2 particles prepared from PhSi(OEt) 3 was increased with increased molecular weight: T g is dependent primarily on the degree of polymerization. The difference in T g shown in Table 1 must be brought about by the difference in the polymerization degree.…”
Section: Characterization Of Polyorganosilsesquiox-mentioning
confidence: 96%
“…95°C). The glass transition temperature is primarily dependent on the degree of polymerization; 23) T g is increased with the increased degree of polymerization. i-BuSi(OEt) 3 has a larger organic substituent (R) and a larger alkoxy group (OR¤) than n-Bu(OMe) 3 ; consequently, the development of three-dimensional siloxane networks of the sample prepared from i-BuSi(OEt) 3 should be prevented.…”
Section: Characterization Of Polyorganosilsesquioxanes With Alkyl Groupsmentioning
confidence: 99%